An Examination of Instructional Approaches in Online Technical Education in Community Colleges - Horvitz, Brian Samuel; Garcia, Lisa R; Garza Mitchell, Regina; Calhoun, Cheryl D (Online Learning, 2019)
Technical education programs in community colleges prepare students for many science and engineering-based jobs in the United States. An increasing number of technical education programs in community colleges are using online learning tools to teach courses. However, little is currently known about the ways these programs are integrating online learning in their coursework. This study examined fifteen National Science Foundation funded technical education programs that use online learning to partially or entirely deliver their courses. We conducted semi-structured interviews with key personnel from each project. Through analysis of this data, we found that technical education programs used a variety of instructional delivery approaches that can be categorized as follows: (a) a hybrid or blended course with asynchronous online lectures; (b) a hybrid or blended course with synchronous lectures; (c) a hybrid or blended course with a combination of asynchronous and synchronous lectures and discussions; or (d) a course that is fully online. We also found that online or hybrid technical education programs used a variety of different methods to give students experience in their field of study that can be categorized as follows: (a) pre-recorded video; (b) live video; (c) simulations; (d) equipment at home; (e) equipment in lab; and (f) professional site experience. We recommend that future research examine how well these approaches are working, incorporate student perceptions, and incorporate the views of employers of these programs’ graduates.